2021
DOI: 10.1101/2021.01.19.426950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control over patch encounters changes foraging behaviour

Abstract: SummaryForaging is a common decision problem in natural environments. When new exploitable sites are always available, a simple optimal strategy is to leave a current site when its return falls below a single average reward rate. Here, we examined foraging in a more structured environment, with a limited number of sites that replenished at different rates and had to be revisited. When participants could choose sites, they visited fast-replenishing sites more often, left sites at higher levels of reward, and ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…It is thus highly doubtful that we are studying choices that are relevant for real world behavior. This is also true for putatively more ecologically valid foraging choices (Constantino & Daw, 2015;Kolling et al, 2012;Shenhav et al, 2016;Yoon, Geary, Ahmed, & Shadmehr, 2018), as demonstrated with the learnable version we reviewed earlier (Hall-McMaster et al, 2021). These studies reveal the additional computations and cognitive resources supporting decision-making that we have so far overlooked, but that are ripe for study.…”
Section: Decisions and Control Over Future Research Directionssupporting
confidence: 57%
See 1 more Smart Citation
“…It is thus highly doubtful that we are studying choices that are relevant for real world behavior. This is also true for putatively more ecologically valid foraging choices (Constantino & Daw, 2015;Kolling et al, 2012;Shenhav et al, 2016;Yoon, Geary, Ahmed, & Shadmehr, 2018), as demonstrated with the learnable version we reviewed earlier (Hall-McMaster et al, 2021). These studies reveal the additional computations and cognitive resources supporting decision-making that we have so far overlooked, but that are ripe for study.…”
Section: Decisions and Control Over Future Research Directionssupporting
confidence: 57%
“…One example is a recent study that modified the standard foraging paradigm, where people need to decide when to abandon a depleting patch for an unknown new one (Kolling et al, 2012;Shenhav et al, 2016; so that people could revisit previous patches and decide where to forage next. Hall-McMaster, Dayan, and Schuck (2021) showed that people learn and represent reward rates of different patches and use this information to choose patches that maximize reward. Importantly, they also leverage information about the rewards at other patches to adaptively adjust decisions about when to leave the current patch.…”
Section: Monitoring Over Multiple Levels Of a Response Hierarchymentioning
confidence: 99%
“…However, theoretical work [ 52 ] shows that for patch foraging agents the optimal strategy should take into account the replenishing rates of unvisited patches. Supported by experimental work [ 53 ] manipulation of replenishing rates on different unvisited patches results in more frequent visits to fast replenishing sites as well as early leaving times in human subjects. While these studies did not examine the role of the choice history effects in maximizing the reward harvesting efficiency, these findings are consistent with our data that behavior of animal (choice history effects) is sensitive to growth rate of probabilities on unchosen options.…”
Section: Discussionmentioning
confidence: 99%
“…by design (Gabay & Apps, 2020;Mormann & Russo, 2021;Yoo et al, 2021). As demonstrated with the learnable version of the foraging paradigm we reviewed earlier (Hall-McMaster et al, 2021), providing people with contextual structure and additional control over their choices provides a new window into how they make them (Constantino & Daw, 2015;Kolling et al, 2012;Shenhav et al, 2016;Yoon, Geary, Ahmed, & Shadmehr, 2018). Taking this route may also shed new light on the computations underlying neural correlates of choice value.…”
Section: Decisions and Control Over Future Research Directionsmentioning
confidence: 98%
“…One example is a recent study that modified the standard foraging paradigm, where people need to decide when to abandon a depleting patch for an unknown new one Shenhav et al, 2016; so that people could revisit previous patches and decide where to forage next. Hall-McMaster, Dayan, and Schuck (2021) showed that people learn and represent reward rates of different patches and use this information to choose patches that maximize reward. Importantly, they also leverage information about the rewards at other patches to adaptively adjust decisions about when to leave the current patch.…”
Section: Monitoring Over Multiple Levels Of a Response Hierarchymentioning
confidence: 99%